My Pet Book - Staake, Bob 1957- (New York : Random House, 2014)
A boy's search for the perfect pet leads him to the bookstore, where he finds a bright red book that becomes his best friend.
Keywords: Books and reading -- Juvenile fiction; Pets -- Juvenile fiction; Friendship -- Juvenile fiction; Books and reading -- Fiction; Pets -- Fiction; Friendship -- Fiction; Stories in rhyme